Effect of Proteolytic Enzymes and Insulin Sensitiser in Treatment of Joint Osteoarthritis in Diabetic Patients - Atia, Yasir A; Al-Thamiree, Safaa Salman; Salah, Shatha; Al-Attar, Zaid (Scripta Medica, 2024)
Background/Aim: Globally, knee osteoarthritis is a frequently crippling chronic condition. Numerous pharmacological medications have been successfully utilised to treat knee osteoarthritis. This research aimed to compare the efficiency of metformin and serratiopeptidase in treating and preventing osteoarthritis development via distinct mechanisms. Methods: Between 1 January and 30 May 2019, a randomised-clinical-trial was done at Al-Kindy Hospital on (two groups) 80 osteoarthritis patients, divided in two groups. Group I was given metformin 850 mg orally, whereas Group II was given serratiopeptidase 20 mg and metformin 850 mg orally. Parameters in these groups were compared with forty healthy normal controls. Results: Following treatment, patients in 2nd group have shown a significant decrease in pain levels (p = 0.001). Interleukin 8 (IL-8), tumour necrosis factor-alpha (TNF-α) and interleukin 1 beta (IL-1ß) levels were significantly decreased in Group II (p = 0.001). Conclusion: The combination of serratiopeptidase and metformin was effective and safe in treating knee osteoarthritis.